1990
DOI: 10.1111/j.1523-1739.1990.tb00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Management Options for Preserving Genetic Diversity: Reintroduction of Guam Rails to the Wild

Abstract: Population management programs recognize the importance of managing genetic diversity in species that are candidates for eventual reintroduction to natural habitats. The planned 1989 release of captive‐born Guam rails (Rallus owstoni), extinct in the wild since 1986, to the Northern Mariana island of Rota provides an opportunity to evaluate various management options for selecting breeders to produce young rails for release. Six options were compared to determine which one best replicated genetic diversity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 26 publications
0
97
0
Order By: Relevance
“…Managers of captive species have found that equalizing the contribution of founders is an effective way to maintain genetic diversity (Haig et al 1990). Feral horses have a harem system, in which one male defends a group of females and fathers their young.…”
Section: Discussionmentioning
confidence: 99%
“…Managers of captive species have found that equalizing the contribution of founders is an effective way to maintain genetic diversity (Haig et al 1990). Feral horses have a harem system, in which one male defends a group of females and fathers their young.…”
Section: Discussionmentioning
confidence: 99%
“…In the development of captive breeding programs, two decisions need to be made: how widely and which individuals should contribute to the progeny and how these individuals should be mated. When the pedigree of the population is available, parent contributions (number of offspring breeding in the next generation) should be optimized by minimizing the global coancestry weighted by those contributions (Haig et al, 1990;Ballou and Lacy, 1995). Minimun coancestry (1) maximizes expected heterozygosity and effective population size Toro, 2000, 2002), (2) is flexible and robust against departures from the ideal conditions (Fernández et al, 2003), (3) minimizes the loss of alleles (Fernández et al, 2004) and (4) preserves the original distribution of allele frequencies (Saura et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…With the expansion of studbook data, the organization of a central body to coordinate captive breeding efforts, emerging methods to amplify and analyze DNA, and the invention of personal computers, population biologists and geneticists began to develop quantitative models for pairing animals to maximize founder contributions and minimize the risk of inbreeding (Haig et al 1990;Ebenhard 1995;Frankham 1995). During this time, there was also a growing recognition of the need for behavioral, physiological, and nutritional considerations in pairing and breeding endangered animals in captivity (Dunn 1986;Kear 1986;Wielebnowski 1998); and by the late 1990s, a modern integrated approach to captive management was in place: Now [in 1998] the need for a broader approach to captive management has been recognized (e.g., Hutchins et al 1995;Maillinson 1995) and research efforts incorporating behavior, nutrition, disease, physiology, genetics, population biology, and various interdisciplinary studies are seen as necessary to facilitate responsible and successful captive propagation and conservation (Wielebnowski 1998, p. 137). This modern integrated approach has resulted in consistently successful breeding programs for some bird groups (e.g., gamebirds, waterfowl, cranes, parrots, raptors, Australian finches [Passeridae], and fringillid finches [Fringillidae]); however, some species have proven difficult to breed in captivity.…”
Section: The Changing Role Of Zoos In the 1960smentioning
confidence: 99%